Morphological and molecular study of L.cyprinacea In Cyprinus carpio from Aghjalar region in Sulaimani province - Nazanin Fadhil (University of Thi-Qar Journal of agricultural research, 2025)
A total of 80 fish (Cyprinus carpio) have been collected from the Aghjalar region in Sulaimani province, Kurdistan region-Iraq . Morphological and light microscopy, as well as the sequencing analysis of (28S rDNA), were used to describe Lernaeacyprinaceain this study. 51 individuals (63.8%) were found to be infested with the ectoparasite Lernaea spp. The overall mean parasite load per infected fish was extremely high, recorded at 14.7 parasites per host, but individuals with even higher numbers of parasites also exist. Molecular analysis results indicate that the PCR product of Lernaeacyprinaceawas 715 bp recorded the highest similarity with (OM835790.1, OM827070.1, OM827069.1, MW423693.1, and MW423694.1) with homology 100%.Our phylogenetic analyses showed that the taxonomic position of the species L. cyprinaceais closely related toLernaeacyprinacea(OM835790.1, OM827070.1, OM827069.1, MW423693.1 and MW423694.1) and Lernaea cruciata(MH982212.1 and MH982215.1). The L. cyprinaceaidentified in our study has the same morphological characteristics as the L. cyprinaceawhich was found for the first time in Iraq.